1999
DOI: 10.1063/1.123460
|View full text |Cite
|
Sign up to set email alerts
|

Depth profiling of GaN by cathodoluminescence microanalysis

Abstract: We present the results of a depth-resolved cathodoluminescence (CL) and transmission electron microscopy study of autodoped GaN grown on sapphire. Depth-resolved CL analysis can be used for depth profiling of the yellow luminescence (YL) center concentration which was found to increase with depth. The results are consistent with the (ON–VGa)2− complex model of YL centers [J. Neugebauer and C. G. Van de Walle, Appl. Phys. Lett. 69, 503 (1996) and T. Mattila and R. M. Nieminen, Phys. Rev. B 55, 9571 (1996)]. Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 15 publications
(20 reference statements)
0
79
0
Order By: Relevance
“…Previous work has suggested as yet unidentified point defects and impurities as an alternative explanation for this blue emission. 20 More recent work provides evidence to correlate broad ϳ2.8 eV emission to the presence of O, in particular a transition from a substitutional oxygen donor (O N ) level to the V Ga -O N complex acceptor. 21 In order to identify the source of near-interface doping and defects, we obtained low temperature ͑10 K͒ CLS and CL images in a cross section of a 5 m-thick sample (A 2 ,n int ϭ1.6ϫ10 15 e/cm 2 ), which was also pretreated with ZnO buffer layer.…”
Section: Low Sheet Carrier Concentrationmentioning
confidence: 99%
“…Previous work has suggested as yet unidentified point defects and impurities as an alternative explanation for this blue emission. 20 More recent work provides evidence to correlate broad ϳ2.8 eV emission to the presence of O, in particular a transition from a substitutional oxygen donor (O N ) level to the V Ga -O N complex acceptor. 21 In order to identify the source of near-interface doping and defects, we obtained low temperature ͑10 K͒ CLS and CL images in a cross section of a 5 m-thick sample (A 2 ,n int ϭ1.6ϫ10 15 e/cm 2 ), which was also pretreated with ZnO buffer layer.…”
Section: Low Sheet Carrier Concentrationmentioning
confidence: 99%
“…To facilitate this measurement a special trigger is being implemented to avoid bias at low B 0 s lifetimes. The collaboration is also preparing for more complex analyses involving tagged and time dependent CP asymmetry studies for B 0 s and B 0 two body decays, which will enable the determination of the CKM γ phase through U-spin symmetry [6].…”
Section: Analysis Plansmentioning
confidence: 99%
“…[23,24]. In the framework of naive factorization or QCD factorization [25], it can be shown that, as long as annihilationtype topologies are small, the double ratio of amplitudes λ (3) breaking.…”
Section: Specific Decaysmentioning
confidence: 99%